Study on the Contact Angle, Adhesion Strength, and Antibacterial Activity of Polymer/Cement Composites for Waterproof Coating - Ibraheim, Sara M.; Hussein, Seenaa I. (Iraqi Journal of Science, 2020)
In the present work, polymeric composites were prepared for coating floors and swimming pools in dark colors. This was achieved through the use of a polymer coating solution added to fine cement with weight percentage (wt%) values of 5, 10, 15, 20, and 25 to obtain dark-colored (gray) composites. Mortar samples were prepared using the adhesion test. The contact angle and adhesion strength were studied for the prepared samples concerning the effect of changing the weight ratio of additive cement on water absorption. Also, the antibacterial activity was tested for the prepared coatings. The results showed that the contact angle increases with increasing the weight ratios of additive cement, which indicates that the prepared coating is not hydrophilic and water-impermeable. Besides, the adhesion was shown to increase with increasing the weight ratio of cement. According to the antibacterial activity analysis, it was found that the highest efficacy for killing Staphylococcus areus was observed at cement ratios of 5 and 15 wt%, whereas no activity was observed against Escherichia coli.